Konflik Norma Mengenai Pengupahan Pada Peraturan Daerah Nomor 22 Tahun 2012 Tentang Sistem Penyelenggaraan Ketenagakerjaan Di Kabupaten Pasuruan - Safana, Holis; Abadi, Suwarno (Law and Humanity, 2024)
Article 88B of the Employment Creation Act expressly stipulates the regulation of workers' wages. In the article there are concepts of wages with results and units of time based on hourly wages. Pasuruan Regency is one of the regencies that has problems with the wage system law. Regional Regulation Number 22 of 2012 namely Article 37 paragraphs 4 and 5 with an additional 5% of the Regency/City Minimum Wage value is synchronized with worker productivity which is a conflict of norms against the implementation of Regional Regulation Number 22 of 2012 concerning the system of labor administration and its enforcement. Implementation of the policy of Regional Regulation Number 22 of 2012 concerning the Employment System in Pasuruan Regency is oriented to the realization of a balance between the interests of the implementer by avoiding potential conflicts over the regulation. This research was conducted using a research method with a conceptual approach and a statutory approach. The research method approaches Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 36 of 2021 concerning Wages which considers the minimum wage. Since the stipulation of District Regulation Number 22 of 2012 concerning the Employment System in Pasuruan Regency, the focus has been on achieving a balance in realizing the interests of the executors by avoiding potential conflicts over these regulations. Legal resolution related to the conflict of norms contained in Regional Regulation Number 22 of 2012 concerning the Employment Implementation System in Pasuruan Regency, which currently can only be reached by mediation.